If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -1(2m + 5) = 3 + 3m + -16 Reorder the terms: 17 + -1(5 + 2m) = 3 + 3m + -16 17 + (5 * -1 + 2m * -1) = 3 + 3m + -16 17 + (-5 + -2m) = 3 + 3m + -16 Combine like terms: 17 + -5 = 12 12 + -2m = 3 + 3m + -16 Reorder the terms: 12 + -2m = 3 + -16 + 3m Combine like terms: 3 + -16 = -13 12 + -2m = -13 + 3m Solving 12 + -2m = -13 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 12 + -2m + -3m = -13 + 3m + -3m Combine like terms: -2m + -3m = -5m 12 + -5m = -13 + 3m + -3m Combine like terms: 3m + -3m = 0 12 + -5m = -13 + 0 12 + -5m = -13 Add '-12' to each side of the equation. 12 + -12 + -5m = -13 + -12 Combine like terms: 12 + -12 = 0 0 + -5m = -13 + -12 -5m = -13 + -12 Combine like terms: -13 + -12 = -25 -5m = -25 Divide each side by '-5'. m = 5 Simplifying m = 5
| 5x(x^2-16)=0 | | 4n^2-14n-15=0 | | 55=22+v | | 2/3a-1/6a+3/5b-3/10b | | 6s^2+15s=0 | | -5x-7=107 | | 0=8n^2-28n-30 | | 2(sy-3)=4(2y+2) | | 0.25(8+4p)-0.5(10+2p)= | | h(h+5)=38 | | 3s+5t=11 | | -21x^2-27x+30= | | -2x^2-17x+55= | | 5x+33=2x+156 | | 36b^2-24b-21=0 | | 3a^2+10ab+3b^2= | | -x^2+30x+900=0 | | -6z+7z=7z-4+4z | | -3/8x=12 | | 151/4X9.35 | | 5-21x+4x^2= | | 2x-2(0)=17 | | r(r-3)(r+5)=0 | | 5-21x-4x^2= | | 7(x-4)=2+8x | | 3+7i/1-3i | | 2(-5)-2y=17 | | 6-4x=7x-9x | | x/3=19.3 | | 10x^2+10=29x | | 570=9000/x+9x | | x^3-14x^2y+24xy^2=0 |